The determinants of dividend payout ratio in Malaysian manufacturing sector / Bibi Nurnashiha Amin - Amin, Bibi Nurnashiha (2016)
Dividend policy is one of the issues in finance area that always been debatable. This dividend issues had captured the attention of many eyes in the world. The purpose of this study is to identify the determinants of dividend payout ratio in Malaysian manufacturing sector. This study contains 30 manufacturing companies which listed in Bursa Malaysia. The data is taking in ten years period from the year 2005 to 2014. Based on the findings, the result show that there a significant and positive relationship between Dividend Payout Ratio and the Cash Flow. Next, the findings show that there is significant but negative relationship between Dividend Payout Ratio and Return on Asset. Then, the result suggests that firstly, the next researchers in the future have to refer more on the past literature to conduct the determinant of dividend payout in Malaysia. Then, they can easily conduct the study on the determinant of dividend payout ratio in differences sector or industry that stated in Malaysia listed companies. Secondly, the investors have to consider about the profitability of the company since the higher the profit, the higher dividend payment to the shareholder. Its proved by the significant level to Return on Asset to Dividend Payout Ratio is 95%.